The Clock affecting 1 mutation of Neurospora is a recurrence of the frq7 mutation7 - Michael A Collett; Jennifer J Loros; Jay C Dunlap (Fungal Genetics Reports, 2001)
The clock affecting-1 (cla-1) mutation of Neurospora crassa increases the period and decreases temperature compensation of the circadian rhythm, and was thought to define an uncloned gene with a possible role in the Neurospora clock. This defect, thought to be due to a translocation, was associated with a slow growth rate and a period of about 27 h at 25cla-1 and found the growth rate and period defects to be due to linked independent mutations. The translocation was not the cause of the long period. The csp-1 mutation, present in the original cla-1 strain, had a period shortening effect, thus cla-1 strains lacking csp-1 had a period length similar to that of frequency7 (frq7). The cla-1 period defect mapped to the frq locus, and sequencing of frq revealed cla-1 to be a re-isolation of frq7.